PENGEMBANGAN ELEKTRONIK - LEMBAR KERJA PESERTA DIDIK BERBANTUAN WEBSITE DIFFIT AI DI MADRASAH TSANAWIYAH AL-IHSANIYAH SARANG BURUNG KABUPATEN MUARO JAMBI - Mely Maudina; Hendra Bestari; Elis Muslimah Nuraida (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2026)
This study aims to develop a learning medium in the form of an electronic student worksheet assisted by the Diffit AI Website, as well as to measure its validity, practicality, and effectiveness. This research is classified as research and development (R&D), employing the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The validation results from media, language, and content experts obtained scores of 85,45% (content expert), 86% (language), and 87,78% ( media expert), all categorized as ‘‘very valid’’. The practicality, based on a small group trial of the learning material, showed a total score of 239 with a percentage of 79,66%, categorized as ‘‘practical’’. The effectiveness of the E-LKPD was demonstrated through the post-test results, with the students average score reaching 81,87%. Based on these findings, it can be concluded that the developed E-LKPD can be used effectively.